Secukinumab provided significant and sustained improvement in the signs and symptoms of ankylosing spondylitis: results from the 52-week, Phase III China-centric study, MEASURE 5 - Huang, Feng; Sun, Fei; Wan, Wei-Guo; Wu, Li-Jun; Dong, Ling-Li; Zhang, Xiao; Kim, Tae-Hwan; Sengupta, Raj; Šenolt, Ladislav; Wang, Yi; Qiu, Hao-Min; Porter, Brian; et al. (Chinese medical journal, 2020)
BACKGROUND: Secukinumab demonstrated sustained efficacy in patients with ankylosing spondylitis (AS) through 5 years in pivotal Phase III studies. Here, we present efficacy and safety results (52-week) of secukinumab in patients with AS from the MEASURE 5 study. METHODS: MEASURE 5 was a 52-week, Phase III, China-centric study. Eligible patients were randomly assigned (2:1) to receive subcutaneous secukinumab 150 mg or placebo weekly for the first five doses and then once every 4 weeks (q4w). All placebo patients switched to secukinumab 150 mg q4w starting at Week 16. Primary endpoint was Assessments of SpondyloArthritis international Society (ASAS) 20 at Week 16. Randomization was stratified by region (China vs. non-China). RESULTS: Of 458 patients (secukinumab 150 mg, N = 305; placebo, N = 153) randomized, 327 (71.4%) were from China and 131 (28.6%) were not from China. Of these, 97.7% and 97.4% patients completed Week 16 and 91.1% and 95.3% (placebo-secukinumab) patients completed Week 52 of treatment. The primary endpoint was met; secukinumab significantly improved ASAS20 response at Week 16 vs. placebo (58.4% vs. 36.6%; P < 0.0001); corresponding rate in the Chinese population was 56.0% vs. 38.5% (P < 0.01). All secondary efficacy endpoints significantly improved with secukinumab 150 mg in the overall population at Week 16; responses were maintained with a trend toward increased efficacy from Week 16 to 52. No new or unexpected safety signals were reported up to Week 52. CONCLUSIONS: Secukinumab 150 mg demonstrated rapid and significant improvement in signs and symptoms of AS. Secukinumab was well tolerated and the safety profile was consistent with previous reports. Efficacy and safety results were comparable between the overall and Chinese populations. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02896127; https://clinicaltrials.gov/ct2/show/NCT02896127?term=NCT02896127&draw=2&rank=1.
Keywords: ankylózující spondylitida; Double-Blind Method; Treatment Outcome; monoklonální protilátky; výsledek terapie; dvojitá slepá metoda; Čína; China; lidé; Humans; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Spondylitis, Ankylosing